Effect of antibiotic batumin on the biofilm formation in staphylococci - Churkina, L.N.; Vaneechoutte, M.; Perunova, N.B.; Luitko, O.B.; Yaroshenko, L.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Antibiotic batumin produced by Pseudomonas batumici has shown high activity against the type and reference strains and clinical isolates of 30 different species of the genus Staphylococcus (including MRSA and SSCVs). Batumin activity against these bacteria was 0.25—0.5 μg/ml. Batumin influence upon the biofilm formation by representatives of genus Staphylococcus has been studied. Presence of 0.125 μg /ml of batumin in the medium decreased the biofilm formation in 85 % of studied strains. Antibiotic effectiveness depended on the stage of its formation. Entry of batumin into the medium simultaneously with the bacterial culture promoted a decrease of the biofilm formation in all studied strains of staphylococci. The formed biofilm was more resistant to antibiotic. Breach of process of biofilm formation under the batumin influence was confirmed by the population analysis of studied staphylococci strains.